2012
DOI: 10.1016/j.foar.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing energy efficiency and occupant comfort with climate specific design of the building

Abstract: Designing energy efficient and comfortable buildings requires harmonizing the complex interactions of architecture, construction and building service engineering. The building envelope has a particular importance, since it integrates many functions and has direct influence on indoor climate. Focusing on satisfaction of the user means that the indoor climate is a key for a holistic design approach. Only a satisfied user will not intervene with the designed energy concept or the indoor climate control; dissatisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…These are the individual buildings (where design for security, comfort, good indoor air and sense of identity (Ghani, 2012;Ibem et al, 2013), energy efficiency of buildings (Menzies and Wherrette, 2005;Mitterer et al, 2012); building form in relation to the site, region, climate and available materials (Ghani, 2012) are examined. Second is the immediate environment where such issues as the presence and/or absence of sources of potential safety threats, the level of social functionality, crowding, exposure to noise and the design and layout of external spaces are investigated (Bonnefoy, 2007).…”
Section: The Concept Of Sustainable Housing Initiativesmentioning
confidence: 99%
“…These are the individual buildings (where design for security, comfort, good indoor air and sense of identity (Ghani, 2012;Ibem et al, 2013), energy efficiency of buildings (Menzies and Wherrette, 2005;Mitterer et al, 2012); building form in relation to the site, region, climate and available materials (Ghani, 2012) are examined. Second is the immediate environment where such issues as the presence and/or absence of sources of potential safety threats, the level of social functionality, crowding, exposure to noise and the design and layout of external spaces are investigated (Bonnefoy, 2007).…”
Section: The Concept Of Sustainable Housing Initiativesmentioning
confidence: 99%
“…Studies of Zeiler and Boxem in 2008 have however shown that sometimes these standards and specifications do not conform to the changing needs and expectations of users; and thus, users are not always satisfied with the performance of their buildings [25]. The consequences of this are manifested in building related illness and 'sick building syndrome' [26], increase in the desire for remodeling or modifications or abandonment of completed buildings [27] which may cause waste of energy and sometimes even damage to the building envelope components and the surrounding environment [28].…”
Section: Social Objectives Of Housing Projectsmentioning
confidence: 99%
“…Moreover, building form is a major factor in a building's aesthetic and visual impact. Some research studies show that design decisions regarding the envelope shape have a direct effect on the energy performance of buildings [9][10][11]. This issue forces architects to come up with improved building design concepts with expensive high-tech solutions [12].…”
Section: Introductionmentioning
confidence: 99%
“…energy performance of buildings [9][10][11]. This issue forces architects to come up with improved building design concepts with expensive high-tech solutions [12].…”
Section: Introductionmentioning
confidence: 99%